AN ANALYSIS OF THE ILLOCUTIONARY FORCE OF A STALKER IN 'CAN I TELL YOU A SECRET?': A FORENSIC LINGUISTICS PERSPECTIVE - Zuhe Safitra; Aceng Ruhendi Saifullah; Syihabuddin Syihabuddin (Universitas Wiralodra, 2024)
This study examines the illocutionary acts used by the stalker in the Netflix docuseries ‘Can I Tell You a Secret?’. Illocutionary acts are analyzed to understand the intended meaning of the stalker’s communication strategies. The objectives of the study are to find out the dominant illocutionary acts used by stalker and their intended meaning. This study employs the qualitative descriptive design and uses the subtitle of the series as its data. The data of the study are taken from the subtitle of the Netflix docuseries ‘Can I Tell You a Secret?’, and then are classified into Searle’s illocutionary act types. The study finds that the stalker commonly uses directive illocutionary acts (49,3%) in his dialogues. This phenomenon shows that the stalker uses his communication strategies to manipulate and control the victim. His strategies also instill fear and doubt in his target. Besides, other types of illocutionary acts are also being employed in stalker’s dialogues. This maintains a continual threat and keeps the victim anxious about what might happen next.